PENGARUH PENGGUNAAN JOBSHEET TERHADAP HASIL BELAJAR PRAKTIKUM KERJA BENGKEL DAN GAMBAR TEKNIK - Vivi Oktavia; Hanesman Hanesman (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the use of jobsheets on student learning outcomes in the workshop workshops and technical drawing of class X Audio Video Engineering. This type of research is quasi-experimental (quasi experiment). The subjects of this study were students of class X TAV of SMK Negeri 1 Koto XI Tarusan who in the 2018/2019 school year consisted of 34 students. Data collection in this study using the results of posttest in the form of objective questions as many as 30 items that have been tested for validity, reliability, index of difficulty and power difference questions. Data that has been obtained is analyzed using two different test averages (t test). From the results of the study obtained the value of the experimental class average of 84.94 and the average value of the control class 75.26. With the analysis of t test, it is obtained tcount = 6.131 which is smaller than t table = 2.037 at the significance level of 0.05. Thus it can be concluded that the use of jobsheet has a significant influence on improving student learning outcomes in the workshop workshops and technical models of class X TAV at SMK Negeri 1 Koto XI TarusanKeywords: jobsheet, workshop work and engineering drawings, Improving Learning Outcomes.